2017
DOI: 10.1161/jaha.117.005658
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Statins Beyond the Initial Period After Stroke and 1‐Year Risk of Recurrent Stroke

Abstract: BackgroundIn‐hospital discontinuation of statins has been linked to poorer early stroke outcomes, but the consequences of postdischarge discontinuation or dose reduction of statin treatment are unknown. The objective of this study was to explore the effects of statin discontinuation or statin dose reduction on recurrent stroke risk.Methods and ResultsWe conducted a nationwide cohort study using the data from the Taiwan National Health Insurance Research Database. Our source population comprised all patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 24 publications
3
17
0
Order By: Relevance
“…Our current work is focused on statins, which exhibit neuroprotective properties independent of their effects on circulating cholesterol (Fang et al, 2015;Zhang et al, 2009). Statins show clinical translation as evidenced by improved post-stroke recovery (Lee et al, 2017;Malhotra et al, 2019;Montaner et al, 2016). Another difference between statins and other compounds believed to be effective in stroke is that statins are known substrates for an endogenous BBB transporter (i.e., OATP1A2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our current work is focused on statins, which exhibit neuroprotective properties independent of their effects on circulating cholesterol (Fang et al, 2015;Zhang et al, 2009). Statins show clinical translation as evidenced by improved post-stroke recovery (Lee et al, 2017;Malhotra et al, 2019;Montaner et al, 2016). Another difference between statins and other compounds believed to be effective in stroke is that statins are known substrates for an endogenous BBB transporter (i.e., OATP1A2).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, 95% of published preclinical studies between 1990 and 2018 on novel neuroprotective drugs for stroke showed positive outcomes; however, none of these compounds have attained clinical success in a Phase III trial (Shi et al, 2018). In contrast, statin administration is associated with a lower degree of physical disability (Ishikawa et al, 2016;Malhotra et al, 2019) or reduced risk of recurrent stroke (Lee et al, 2017). Our work has demonstrated that Oatp1a4 can facilitate CNS delivery of both hydrophilic statins (i.e., pravastatin) and hydrophobic statins (i.e., atorvastatin) (Abdullahi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Statins also improve outcomes in patients after stroke onset. For example, atorvastatin is associated with reduced risk of recurrent stroke in patients with a recent stroke or transient ischemic attack [102,103]. In a study of 104 patients receiving intravenous (i.v.)…”
Section: Neuroprotective Properties Of Statins In Strokementioning
confidence: 99%
“…8,9 Additionally, although high-intensity statin therapy has been suggested to decrease major adverse limb events in peripheral vascular disease, the effect of highintensity statin has not been compared with moderate intensity regimens in patients after CEA. 11 Some have suggested a possible increased benefit of high-intensity statin therapy in carotid disease, 12,[23][24][25][26][27] with some evidence of plaque stabilization as well as a decreased carotid intima media thickness. Yu et al 27 saw regression of carotid atherosclerotic disease with high-dose compared with low-dose atorvastatin.…”
Section: Journal Of Vascular Surgerymentioning
confidence: 99%